Effect of Mengkudu Leaf Extract on Blood Profile of Quail Starter - T. M. Wardiny; Y. Retnani; . Taryati (Jurnal Ilmu dan Teknologi Peternakan, 2012)
The research was designed to evaluate the effect of addition of mengkudu (Morinda citrifolia) leaf extract as antibacteria of Salmonella typhimurium in drinking water during starter period (1-4 weeks) on blood profile of Japanese quail. Mengkudu leaf extract obtained from the leaves of Morinda citrifolia, which are dried, then boiled in water for 26 minutes with ratio between dried leaf and water 1:1. A completely randomized design (CRD) was used to analyze the data obtained from this research. Two hundred and fourty Day Old Quails with average body weight 7,73-8,08 g were divided into 4 treatment groups with 3 replications and 20 quails in each replicate. The treatments were R0 (quail drink was given multi-vitamin), R1 (quail drink was given 5% of mengkudu leaf extract), R2 (quail drink was given 10% mengkudu leaf extract) and R3 (quail drink was given 15% mengkudu leaf extract). The haematological parameters observed were erythrocyte number, haemoglobin level, haematocrit, and leucocyte number. The result of the research showed that the erythrocyte number, haemoglobin level, hematocrit and leucocyte number were not significantly different (P>0,05) for all treatments. Although the statistical parameters of the observations due to treatment not give significantly different results, but when viewed from the average parameters, treatment containing 15% mengkudu leaf extract (R3) gives the best results. Because it can increase hemoglobin levels, leukocyte count and blood hematocrit values were within the normal range for quail. So that 15% mengkudu leaf extract (R3) in drinking water can be used as alternative herbal feed additive instead of antibiotics